2013
DOI: 10.7589/2012-03-079
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Swine H1 and H3 and Avian H5 and H9 Influenza a Viruses Among Feral Swine in Southern China, 2009

Abstract: ABSTRACT:Swine play an important role in the disease ecology of influenza. Swine may provide the potential for mixed infections and genetic reassortment between avian, human, and porcine influenza viruses. We investigated the prevalence of antibodies to swine H1 and H3 influenza viruses and avian H5 and H9 influenza viruses in feral swine in southern China. Serum samples were collected from 31 feral swine harvested in 2009 in southern China. Of 31 serum samples tested, 14 (45%) had detectable antibody to H1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The seroprevalence of IAV among wild boars varies from 0% in Finland, France and Slovenia, up to 74% in China [1, 3, 8, 19, 22, 23]. In this study, the seroprevalence of IAV in wild boars was lower than in domestic pigs (8.4–22.7%) in Japan [18].…”
mentioning
confidence: 61%
“…The seroprevalence of IAV among wild boars varies from 0% in Finland, France and Slovenia, up to 74% in China [1, 3, 8, 19, 22, 23]. In this study, the seroprevalence of IAV in wild boars was lower than in domestic pigs (8.4–22.7%) in Japan [18].…”
mentioning
confidence: 61%
“…After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic‐related strains was found to be much higher than those against other subtypes of IAVs . Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars . These serological surveys suggest that wild boars can serve as mixing vessels for IAVs, and potential sources for novel pandemic strains.…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 99%
“…Swine influenza, a zoonosis, is relatively common in domestic pigs worldwide, but exposure of wild pigs is not ubiquitous and varies geographically (Smith et al, 2009). While prevalence was high in a study in southern China (Luo et al, 2013), in Korea, the US and Spain, seroprevalence was generally low (< 20%) and varied seasonally; it is possible that our sample size was insufficient to detect exposure in Guam (Hall et al, 2008;Corn et al, 2009;Feng et al, 2014). Enteric and respiratory coronaviruses, which have been reported in several Asian countries, are of significant concern due to high morbidity and mortality in naïve pig populations (Song and Park, 2012).…”
Section: Discussionmentioning
confidence: 99%